The coronavirus prevention handbook 101 science-based tips that could save your life - Zhu, Shan; Chen, Qing; Li, Jun; Zhou, Wang; Zhou, Wang (Physician) (Skyhorse, 2020)
The Coronavirus Prevention Handbook is a comprehensive guide, written by Wang Zhou and a panel of experts at the center of the coronavirus pneumonic epidemic (COVID-19). With graphic illustrations and plain language, this book is an introduction to COVID-19 that anyone can understand and use to safeguard themselves against the pandemic. As COVID-19 continues to spread around the world, preventative measures such as controlling the source of infection, early detection of patients, and cutting off transmission become more imperative. With 101 tips for individuals to prevent the spread of the coronavirus, the information in this handbook could be lifesaving